Simultaneous doping of nitrogen, sulfur and fluorine into Reduced Graphene Oxide and Its Electrochemical Properties - Agung Nugroho; Izzan Fariz Rahman; Farhan Erviansyah; Nur Layli Amanah; Yohana Fransiska Ferawati; Arenst Andreas Arie; Ratna Frida Susanti (Journal of Applied Science and Engineering)
One possible approach to improve the electrochemical properties of reduced graphene oxide (rGO) is the heteroatom doping strategy. Usually, just one or two atom doping can boost electrode performance. We opted to see if three-atom doping can further improve performance. We simultaneously doped three atoms (N, F and S) into the rGO structure using thiourea and ammonium fluoride as dopant precursors with the hydrothermal method. Three-atom doping via C-N, C-S, and C-F bonds was verified by X-ray photoelectron spectrum (XPS) study. Moreover, Energy Dispersive X-ray (EDX) mapping showed a homogeneous distribution of S (13.96%), N (5.66%), and F (0.62%). The electrochemical investigation revealed that NSF-rGO outperformed pristine rGO, with a specific capacitance of 601.33 F/g at 1 A/g, exceeding undoped rGO ( 578.67 F/g ). These results suggest that three-atom doping might be beneficial approach to improve rGO properties, therefore generating a suitable electrode material for use in energy storage.